Live fast, die young, become immortal - Ellis, Katie (Chandos Publishing is an imprint of Woodhead Publishing Limited., 2012)
There are many ways in which to mark death, particularly the death of a celebrity. However, social media and the capacities of the read write web have enabled fans to memorialise and remember dead celebrities in new and often strange ways. This chapter explores the online response to the unexpected death of Heath Ledger. Although pre-dating the online frenzy created from Michael Jackson's death, the way in which fans eulogise and create e-memorials remains an area to monitor and research.